Russia and Canada to ratify Kyoto Protocol. - Yu-Tzu Chiu (IEEE spectrum)
Announcements at Johannesburg earth summit appear to guarantee the agreement will take force at the end of this year. The Kyoto protocol, which requires industrial countries to reduce greenhouse gas emissions and offers developing countries incentives to do the same, was adopted in 1997 as an implementation amendment to the UN Framework Convention on Climate Change. That treaty was adopted at the last earth summit dedicated to sustainable development, in Rio in 1992. The Kyoto Protocol takes force only if ratified by countries contributing 55 percent of the worlds unwanted gas emissions. Russia's statement of intent, together with a similar statement from Canada, seems to guarantee that this criterion will be satisfied. Russia's decision to join the Kyoto regime was hardly a surprise. Because of the economic depression the country suffered after the collapse of Soviet communism, its greenhouse gas emissions have dropped drastically, so that the country already in effect has met Kyoto targets. More significant, perhaps, was Canada's decision to also seek ratification of the agreement. The Kyoto Protocol still faces opposition from some of Canada's provincial governments, but given the country's parliamentary system, in which the will of the governing majority normally holds sway, ratification seems very nearly assured.